CRISTIANISMO ETÍOPE A PARTIR DA EXPERIÊNCIA ÉTNICA NARRADA EM ATOS 8, 26-40 - Izidoro, José Luiz (2005)
In recent times, it has become very important to explicitate the Christian experiences that existed in and co-existed with, or even were immersed in the extrapalestinian cultures, and which were protagonists in the project of the proclamation of the Christian kerygma. Those experiences were lived and realized in the period of Early Christianity and, without a doubt, contributed significantly to its expansion process. We present the passage of Acts 8,26-40, the episode of Philip and the Ethiopia n. What happens here is a dislocation of the missionary-geographical axis from Samaria to the way that goes down from Jerusalem to Gaza , and reaching back to Caesarea. The text opens up the horizon of Christian experiences to other peoples and nations represented in the figure of the Ethiopian eunuch. Taking Acts 8,26-40 in its Lucan redaction as a starting point, using exegetical methods and historical-literary resources, based on the theoretical reference to the concepts of ethnicity and ethnic boundaries, we intend to investigate the possibility of a Christian experience lived in Ethiopia, which constructed itself ethnically from the identities that interacted in the text, and which points out to the imaginary of Ethiopia s symbolic universe. Doing so, we reclaim, within Biblical Exegesis, hermeutical issues for our own theological, biblical, and pastoral practice, on the horizon of the identities and ethnic boundaries of the Africanamerican and Caribian universe.